Exploring the structure–reactivity relationship of sn-Cr binary catalysts with XRD extrapolation method: The vital role of surface O2− and acidic sites for toluene combustion. (1st May 2023) - Yan, Haiming; Lv, Yu; Xing, Tianyi; Zhang, Shijing; Xu, Xianglan; Xu, Junwei; Fang, Xiuzhong; Wang, Xiang
Graphical abstract: Highlights: Cr 3+ can dissolve in SnO2 to form non-continuous tetragonal solid solutions. The lattice capacity of Cr 3+ in SnO2 is with a Sn/Cr mole ratio of 7/3. Catalysts near the lattice capacity display the best toluene combustion activity. These catalysts form the largest amount of surface active O2 − and acidic sites. Abstract: To explore the structure–reactivity relationship of solid solutions and design effective catalysts for toluene combustion, Sn-Cr catalysts with varied Sn/Cr mole ratios have been fabricated by a co-precipitation method. With various techniques, the crystalline and surface features, and the Cr distributions have been investigated. By adopting XRD and XPS extrapolation methods, it is found that lattice capacity of Cr 3+ in SnO2 matrix is 0.210 g Cr2 O3 /g SnO2, being equal to a Sn/Cr mole ratio of 7/3. If the Cr content is above this capacity, Cr2 O3 species/crystallites will be formed. The catalysts (SnCr7-3 and SnCr6-4) with Cr contents around the lattice capacity possess the largest quantities of surface active O2 − anions and acidic sites, thus showing the highest intrinsic catalytic activity. The synergistic action between these surface two active sites determines the activity of Sn-Cr catalysts. It is proposed that the optimal catalyst can be prepared by doping the SnO2 matrix with capacity quantity of Cr 3+, which can form the largest amount of pure sn-Cr solid solution phase in the structure.